Change and Continuity: The Kompilasi and Indonesian Islamic Courts' - Euis Nurlaelawati (Studia Islamika, 2007)
This paper takes a closer look at judicial practices and judgments in the Indonesian Islamic courts since the introduction of Kompilasi (full title: Kompilasi Hukum Indonesia, KHI). The Kompilasi covers Islamic legal rules, particularly family law, derived from various fiqh texts. The Kompilasi is divided into three books. Book One addresses marriage and divorce law. Book Two covers inheritance. Book Three is about endowment (waqf) . The material is subdivided by topic into books, chapters, and articles, beginning with a chapter addressing general provisions, followed by chapters treating specific subject areas in each book.DOI: 10.15408/sdi.v14i1.559